2017
DOI: 10.1103/physrevlett.118.022002
|View full text |Cite
|
Sign up to set email alerts
|

Isoscalar ππ Scattering and the σ Meson Resonance from QCD

Abstract: We present for the first time a determination of the energy dependence of the isoscalar ππ elastic scattering phase-shift within a first-principles numerical lattice approach to QCD. Hadronic correlation functions are computed including all required quark propagation diagrams, and from these the discrete spectrum of states in the finite volume defined by the lattice boundary is extracted. From the volume dependence of the spectrum we obtain the S-wave phase-shift up to the KK threshold. Calculations are perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
235
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(250 citation statements)
references
References 82 publications
15
235
0
Order By: Relevance
“…34 can be compared with the σ-meson mass extracted from mesonic sector calculations to test the heuristic arguments above that lighter excitations will make volumesuppressed contributions. Calculations of the σ-meson face a severe StN problem, particularly at light quark masses where the σ-meson describes a broad ππ isoscalar resonance rather than a compact QCD bound state, but a recent calculation by the Hadron Spectrum collaboration has precisely determined M σ = 758(4) MeV at m π ∼ 391 MeV where the σ-meson is weakly bound [45]. Similarly precise results at slightly higher quark masses are not available for interpolation to m π ∼ 450 MeV, but a crude extrapolation can be made using the Hadron Spectrum result and the (real part of the) physical position of the σ-meson pole obtained from dispersive analysis of experimental data: M σ = 457(14) MeV [46,47].…”
Section: An Improved Estimatormentioning
confidence: 99%
“…34 can be compared with the σ-meson mass extracted from mesonic sector calculations to test the heuristic arguments above that lighter excitations will make volumesuppressed contributions. Calculations of the σ-meson face a severe StN problem, particularly at light quark masses where the σ-meson describes a broad ππ isoscalar resonance rather than a compact QCD bound state, but a recent calculation by the Hadron Spectrum collaboration has precisely determined M σ = 758(4) MeV at m π ∼ 391 MeV where the σ-meson is weakly bound [45]. Similarly precise results at slightly higher quark masses are not available for interpolation to m π ∼ 450 MeV, but a crude extrapolation can be made using the Hadron Spectrum result and the (real part of the) physical position of the σ-meson pole obtained from dispersive analysis of experimental data: M σ = 457(14) MeV [46,47].…”
Section: An Improved Estimatormentioning
confidence: 99%
“…In particular, the Lüscher method and its extensions for relating finite-volume spectra to scattering amplitudes are now well established for elastic [5][6][7][8][9][10][11][12][13][14] and coupled-channel [15][16][17][18][19] hadron-hadron scattering. These methods have been demonstrated in a number of applications, notably for the ρ-resonance seen in P -wave ππ scattering [20][21][22][23][24][25][26][27][28][29], and for the σ resonance seen in S-wave ππ scattering [30]. It has also recently been shown that, with sufficiently extensive and precise spectra, information on coupled-channel hadron-hadron scattering amplitudes can be obtained [26,[31][32][33] -this is crucial for understanding highly excited states that are typically kinematically permitted to decay into several channels.…”
Section: Jhep10(2016)011mentioning
confidence: 99%
“…The authors of Ref. [14] on the other hand extracted many energy eigenstates in the corresponding channel and obtained the scattering amplitudes for two values of pion mass -236 MeV and 391 MeV. The information about the σ meson is deduced from the pole structure Ref.…”
Section: Introductionmentioning
confidence: 99%
“…For the isospin-0 channel the situation is more complicated mainly due to the fermionic disconnected diagrams contributing here, which are challenging to compute in lattice QCD. To date there are only two full lattice QCD computations dedicated to this channel [11,14]. In Ref.…”
Section: Introductionmentioning
confidence: 99%